درجة رضا طلبة المدارس الثانوية في مديرية التربية والتعليم للواء قصبة إربد عن الخدمات التعليمية التعلمية - الغول، كاظم عادل أحمد (دار سمات للدراسات والأبحاث, 2016)
هدفت الدراسة إلى التعرف على درجة رضا طلبة المدارس الثانوية عن الخدمات التعليمية التعلمية المقدمة لهم، وتحديداً درجة رضاهم عن المرافق التعليمية المساندة، والهيئة التدريسية والإدارية، والمواد الدراسية والوسائل التعليمية بلغت عينة الدراسة (513) طالب وطالبة من المرحلة الثانوية. وتبين من النتائج "الرضا إلى حد ما "من طلبة المرحلة الثانوية عن :مختبرات الحاسوب وعدد الأجهزة بها وسلامتها، ومستوى تجهيزات مختبر العلوم) أحياء، فيزياء، وكيمياء(،وتنوع ومناسبة الكتب في المكتبة المدرسية لمستوى الطلبة، ونشاط الإدارة المدرسية، وعدد المعلمين وتعاملهم وأسلوب تدريسهم، وعدد ومحتويات الكتب المدرسية. في المقابل عبر الطلاب عن "عدم رضاهم " عن: مستوى تجهيزات المشغل المهني) النشاط(، ومستوى تجهيزات المرسم) غرفة الفن(، ومستوى تجهيزات غرفة الموسيقى. وحجم الكتب المدرسية )عدد الصفحات(، ووجود وتنوع الوسائل التعليمية المساندة )لوحات، مسجل...(.كما أبدى الطلبة عدم رغبتهم بزيادة عدد المواد العلمية والأدبية على حد سواء وأظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (a= 0.05) بين متوسط استجابات طلبة المدارس الثانوية نحو: 1. المرافق التعليمية المساندة وفقاً لمتغير النوع، الصف، والمسار التعليمي؛ وذلك لصالح الإناث، وطلبة الصف الأول ثانوي، وطلبة المسار الأدبي. 2. الهيئة التدريسية والإدارية وفقاً لمتغير النوع، الصف، والمسار التعليمي؛ وذلك لصالح الإناث، وطلبة الصف الأول ثانوي، وطلبة المسار الأدبي. 3. المواد والوسائل التعليمية وفقاً لمتغير المسار التعليمي؛ وذلك لصالح طلبة المسار الأدبي. وتجدر الإشارة إلى عدم حصول أي عبارة من عبارات الاستبانة على متوسط استجابة بدرجة " راض"، واقتصر متوسط درجات استجابات الرضا على " راض إلى حد ما"، و"غير راض".
The study aimed at identifying the level of secondary school students’ satisfaction regarding the teaching-learning services offered to them; especially the level of their satisfaction concerning the educational support facilities, teaching and administrative staff, textbooks, and audio-visual aids. The population of the study consisted of (513) male and female secondary stage students. The findings showed that they are “relatively satisfied” with: computer labs, the number of PCs in the labs, and their safety; the science (biology, physics, chemistry) lab equipment; the variety and convenience of the books in the school library in terms of students’ level; administration hard-work, number of teachers, their way of treatment, their teaching methods, and the number and content of school textbooks. On the other hand, the students expressed their “dissatisfaction” regarding: the vocational (activities) lab equipment, art room equipment, music room equipment, size (number of pages) of textbooks, and the availability and variety of educational support audio-visual aids (boards, cassette players,…). They also expressed their unwillingness to increase the number of subjects (scientific and literary) as well. Moreover, the findings showed differences with statistical significance at the significance level (a=0,05) among the secondary school students’ responses medium as follows: 1. Educational support facilities according to the genre variable, grade, and educational stream for the benefit of female students, first secondary school students, and literary stream students. 2. Administrative and teaching staff according to the genre variable, grade, educational stream for the benefit of female students, first secondary school students, and literary stream students. 3. Educational materials and audio-visual aids based on the educational stream for the benefit of the literary stream students. It was noted that none of the questionnaire statements received a medium level response as “satisfied”. The medium level of responses related to satisfaction ranged between “relatively satisfied” and “dissatisfied”.
Keywords: المرافق التعليمية المساندة -- الوسائل التعليمية -- المناهج الدراسية -- التعليم -- المعلم -- مدير المدرسة